Deracemization and Stereoinversion of Alcohols Using Two Mutants of Secondary Alcohol Dehydrogenase from Thermoanaerobacter pseudoethanolicus. Issue 30 (16th July 2020) - Nafiu, Sodiq A.; Takahashi, Masateru; Takahashi, Etsuko; Hamdan, Samir M.; Musa, Musa M.
Abstract : We developed a one‐pot sequential two‐step deracemization approach to chiral alcohols using two mutants of Thermoanaerobacter pseudoethanolicus secondary alcohol dehydrogenase ( Te SADH). This approach relies on consecutive non‐stereospecific oxidation of alcohols and stereoselective reduction of their prochiral ketones using two mutants of Te SADH with poor and good stereoselectivities, respectively. More specifically, W110G Te SADH enables a non‐stereospecific oxidation of alcohol racemates to their corresponding prochiral ketones, followed by W110V Te SADH‐catalyzed stereoselective reduction of the resultant ketone intermediates to enantiopure ( S )‐configured alcohols in up to > 99 % enantiomeric excess. A heat treatment after the oxidation step was required to avoid the interference of the marginally stereoselective W110G Te SADH in the reduction step; this heat treatment was eliminated by using sol‐gel encapsulated W110G Te SADH in the oxidation step. Moreover, this bi‐enzymatic approach was implemented in the stereoinversion of ( R )‐configured alcohols, and ( S )‐configured alcohols with up to > 99 % enantiomeric excess were obtained by this Mitsunobu‐like stereoinversion reaction. Abstract : A one‐pot two‐step deracemization approach for alcohols that uses two mutants of Thermoanaerobacter pseudoethanolicus secondary alcohol dehydrogenase that exhibit different extents of stereoselectivity is reported. This approach is also used in stereoinversion of ( R )‐alcohols (i.e., Mitsunobu‐like reaction).